2013
DOI: 10.1039/c3ee00052d
|View full text |Cite
|
Sign up to set email alerts
|

The nanostructure of three-dimensional scaffolds enhances the current density of microbial bioelectrochemical systems

Abstract: Bioelectrochemical systems encompass a range of electrochemical systems wherein microorganisms are used as biocatalysts. These range from classical microbial fuel cells to novel microbial electrosynthesis processes. The future of practical applications relies on increased performance. In all cases the development of new electrode materials is essential to overcome the low current densities of bioelectrochemical systems. Here we describe a new biocompatible, highly conductive three-dimensional scaffold electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 35 publications
(74 reference statements)
3
118
0
1
Order By: Relevance
“…[29,115]. As shown in Figure 20, the nanoweb can cover the RVC structure uniformly, providing additional surface area for chemical or biological functionalization.…”
Section: Modified Rvc Electrodesmentioning
confidence: 97%
See 1 more Smart Citation
“…[29,115]. As shown in Figure 20, the nanoweb can cover the RVC structure uniformly, providing additional surface area for chemical or biological functionalization.…”
Section: Modified Rvc Electrodesmentioning
confidence: 97%
“…As pointed out by the authors, RVC electrodes have found application in microbial fuel cells due to their biocompatibility, high surface area, low cost and high conductivity. Furthermore, recent advances have incorporated advanced materials such as carbon nanotubes to form hierarchical "nanowebs" within the RVC structure [29,115]. Uniform biofilms could develop on this substrate, resulting in an increased activity towards acetate degradation in comparison to bare RVC, reaching current densities up to 6.8 mA cm −2 even in the absence of electrolyte flow.…”
Section: Fuel Cellsmentioning
confidence: 99%
“…foam material of honeycomb structure that has also been used in few microbial fuel cell studies [116,[146][147][148]. RVC has a number of advantages for bioelectrochemical systems such as a very high surface area to volume ratio, high electrical conductivity, strong chemical and heat resistance and minimal reactivity over a wide range of conditions [150].…”
Section: Reticulated Vitreous Carbon (Rvc) Is a Rather Cheap And Commmentioning
confidence: 99%
“…Roughened surfaces offer greater surface and provide more favourable sites for colonization. Increasing the available surface area for biofilm growth by using rough or porous materials is a well-proven strategy for MFC performance enhancement [116,117,127,[146][147][148].…”
Section: Bioanode Electrode Materials -A Brief Overviewmentioning
confidence: 99%
“…Materials science recently shows promising progress in providing cheaper electrode materials that feature improved surface properties to increase electron transfer rates. [78][79][80] But before general process design steps can be approached a better understanding of the overall net benefits of possible processes of interest is needed.…”
mentioning
confidence: 99%